Discrete event simulation to reduce patient waiting time problems in the emergency department - Ab Rahmin, Nor Aliza; Rosali, Haliza; Mat Hasim, Risman; Fuzail, Siti Khadijah (UPM, 2024)
Emergency department is one of the busiest department in the hospital. In this project, we use Discrete Event Simulation (DES) to discover patient flow in the emergency department (ED) and at the same time to minimize the patient waiting times. There are three queues that have been considered which are triage, general assessment and additional examination with human resources (nurses and physicians). The positive outcomes observed and it shows significant improvements in average waiting times for various scenarios. Moreover, comparisons between different cases highlight the potential of DES, showcasing noteworthy reductions in waiting times when doubling patient loads. The findings emphasize the transformative impact of integrating DES into emergency department management, offering valuable insights for healthcare systems aiming to optimize resources and improve overall quality of ED.